2012
DOI: 10.4103/2278-330x.103714
|View full text |Cite
|
Sign up to set email alerts
|

The role of honey in healing of bedsores in cancer patients

Abstract: Background:Honey was used to treat infected wounds as long as 2000 years before bacteria were discovered. It has been reported to have inhibitory action to around 50 species of bacteria and fungi (aspergillus, penicillium). Usually, Metronidazole powder is used in our palliative clinic for wound healing due to low cost & effectivity. Honey is cheap, easily available ingredient with high astringent activity.Objective:Objectives of the study were to find out the effectiveness of Honey in terms of rate of wound h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…An activity closely linked to antibacterial capacity is wound healing. The ability of honey to sterilize the wounds, stimulate tissue re-growth, and to reduce edema and scar formation, affects simple wounds, burns, diabetic foot ulcers, and pressure ulcers [ 6 , 58 , 59 ].…”
Section: Honey and Health And Diseasesmentioning
confidence: 99%
“…An activity closely linked to antibacterial capacity is wound healing. The ability of honey to sterilize the wounds, stimulate tissue re-growth, and to reduce edema and scar formation, affects simple wounds, burns, diabetic foot ulcers, and pressure ulcers [ 6 , 58 , 59 ].…”
Section: Honey and Health And Diseasesmentioning
confidence: 99%
“…Bee honey has been used for centuries as a nutritional, preventive, and medicinal product. Over the past 10 year, its use has been studied in the following diseases: arthritis [ 3 ], breast cancer (cell line) [ 4 ], cervical cancer (cell line) [ 4 ], colon cancer (cell line) [ 5 ], cough [ 6 ], type 2 diabetes [ 7 ], hepatic steatosis [ 8 ], influenza [ 9 ], glioblastoma multiforme (cell line) [ 10 ], Helicobacter pylori [ 11 ], mucositis [ 12 ], osteoporosis [ 13 ], pressure ulcers [ 14 ], Pseudomonas [ 15 ], renal cancer cell line [ 16 ], and rosacea [ 17 ]. Due to such diverse activity, honey must be of the highest quality [ 1 , 2 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Also, a study by Soha showed that honey could be used as an effective and safe material for covering the bedsores of patients. [ 16 ] Dorjsembe found that, Achillea asiatica extract significantly increased epithelialization and accelerated skin wound healing in rats. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%